Does religiosity drive sustainability? Analyzing the impact of religiosity on sustainability behaviors among Muslim consumers in Pakistan - Muhammad Zafran (Discover Sustainability)
Abstract The notion of sustainability is at the forefront of business and society at large. Excessive use of resources promoting ecological behaviors can’t be ignored from religious perspective. The literature shows inconclusive findings about the influence of religiosity on sustainable behaviors, and prior studies on religiosity are context- or culture-specific. Little attention has been paid to Islamic religiosity and sustainability behaviors. The purpose of this study is to examine whether religiosity drives sustainability behaviors among Muslims in the cultural context of Pakistan. Drawing on the theory of planned behavior (TPB), this study aims to investigate the impact of intrinsic and extrinsic religiosity on sustainability behaviors such as (a) energy saving, (b) recycling, (c) concern for the environment, and (d) sustainable consumption behavior/quality of life. The research framework also includes a moderating role of “social status desire (SSD)” to determine whether SSD moderates the relationship between religiosity and sustainability behaviors. A quantitative method was used, administering 225 survey forms to collect sample data from individuals across Punjab, Pakistan. The survey results show that both intrinsic and extrinsic religiosity have a direct positive impact on all dimensions of sustainability behavior except extrinsic religiosity, which has a non-significant impact on environmental concern. Further, moderation analysis reveals that social status desire (SSD) positively moderates the relationship between intrinsic religiosity and energy saving and sustainable consumption behavior, while no moderating effect was found on recycling behavior and environmental concern. In contrast, SSD showed significant but negative moderating effects for all four dimensions of sustainability behavior. The study findings have important implications for promoting sustainability behavior using religions as a powerful force for changing behavior and environmental conservation.